"You can do it yourself and you can do it at your convenience": internet accessibility and willingness of people with chronic breathlessness to use an internet-based breathlessness self-management intervention during the COVID-19 pandemic. Issue 1 (21st February 2022) - Reilly, Charles C.; Bristowe, Katherine; Roach, Anna; Maddocks, Matthew; Higginson, Irene J.
Introduction: The burden of chronic breathlessness on individuals, family, society and health systems is significant, and set to increase exponentially with population ageing, complex multimorbidity and coronavirus disease 2019 (COVID-19)-related disability. Breathlessness support services are effective; however, reach and access are limited. Delivering online breathlessness interventions may build capacity and resilience within health systems to tackle chronic breathlessness through supported self-management. The aim of this study was to explore accessibility and willingness of patients with chronic breathlessness to use an internet-based breathlessness self-management intervention (SELF-BREATHE). Methods: Semi-structured telephone interviews were conducted with adults living with advanced malignant and non-malignant disease and chronic breathlessness (July to November 2020). Interviews were analysed using conventional and summative content analysis. Results: 25 patients (COPD: n=13; lung cancer: n=8; interstitial lung disease (ILD): n=3; bronchiectasis: n=1) were interviewed: 17 male, median (range) age 70 (47–86) years and Medical Research Council dyspnoea score 3 (2–5). 21 patients had internet access. Participants described greater use, acceptance and normalisation of the internet since the advent of the COVID-19 pandemic. They described multifaceted internet use: functional, self-investment (improving health and wellbeing) and social. The concept of SELF-BREATHE was highly valued, and most participants with internet access were willing to use it. In addition to technical limitations, personal choice and perceived value of the internet were important factors that underpinned readiness to use online resources. Conclusion: These findings suggest that patients living with chronic breathlessness that have access to the internet would have the potential to benefit from the online SELF-BREATHE intervention, if given the opportunity. These findings suggest that patients living with chronic breathlessness that have access to the internet would have the potential to benefit from the online SELF-BREATHE intervention, if given the opportunity https://bit.ly/3tdJYru